Early Enteral Feeding Strategies and Risk of Necrotizing Enterocolitis in Preterm Neonates: A Cohort Study - Chowdhury, Mahmudul Hoque; Islam, Thrina (Journal of Rangpur Medical College, 2026)
Background: Necrotizing enterocolitis (NEC) is a serious inflammatory bowel disease that affects preterm newborns. It has a high rate of illness and death, especially in babies who are very low birth weight. Objective: To assess the correlation between exclusive human milk (EHM) feeding in the initial 14 days of life and the incidence of necrotizing enterocolitis (NEC) in preterm neonates. Methods: A prospective cohort study was conducted Bangladesh Shishu Hospital & Institute, Dhaka involving 95 preterm neonates (<37 weeks). The neonates were categorized into two groups: EHM and non-EHM. Feeding habits, probiotic use, parenteral nutrition, and clinical outcomes were recorded. NEC incidence (Bell stage II/III), late-onset sepsis, time to full feeds, and mortality were analyzed using risk ratios, Kaplan–Meier survival analysis, and multivariable Poisson regression. Results: Neonates who were fed EHM started eating earlier, took longer to finish their meals, and used more probiotics. The rate of NEC was lower in the EHM group (5.2%) than in the non-EHM group (18.9%; RR=3.65, 95% CI 1.01–13.16, p=0.041). Feeding without EHM, being born very early, and quickly moving up the feeding schedule all raised the risk of NEC. On the other hand, antenatal steroids and probiotics were protective. EHM babies also had fewer cases of late-onset sepsis, got full feeds faster, and lived longer. Conclusion: Feeding only human milk to preterm neonates for the first 14 days greatly lowers the risk of NEC and improves clinical outcomes. J Rang Med Col.2026 Mar;11(1): 99-104